The Art of Uncertainty: Unreliability and Ambiguity in Agatha Christie’s Mysteries Novels - Sabr, Azhar Kadhim; Jubair, Dr. Ahmed Karyosh (Thi Qar Arts Journal, 2024)
The current paper deals with unreliability and ambiguity in the style of novels by Agatha Christie. This paper sheds light on two important issues. Firstly, investigate the use of manipulating techniques in Agatha Christie’s novels. Secondly, please find out how Christie used an unreliable narrator as one of the common techniques of the mystery genre to manipulate the words and make sense of ambiguity in her detective novels. The paper has come out with certain concluding points. Firstly, unreliability is used in detective fiction to mislead readers by introducing them to unexpected story developments, such as the metamorphosis of apparently trusted or reliable individuals into unreliable ones. Secondly, Christie uses the unreliability of her unreliable narrator, who called Dr. Sheppard in her novel 'The Murder of Roger Ackroyd', to hide his identity as a killer, only revealing it at the end. Thirdly, in 'Sing a Song of Sixpence', Christie used certain modal verbs to hide the real killer and make the responsibility lie on the family members themselves, not the outsiders. We know that Christie manipulates the ideas and changes the facts by claiming that the ones who should be responsible for the murder are the house members. In sum, Agatha Christie’s style of novels is full of unreliability and ambiguity. She used to use such techniques to manipulate the readers’ minds, thoughts, and even feelings. The conclusions arrived at have validated the above hypothesis. This paper stated two hypotheses: The first is that an unreliable narrator can make a sense of ambiguity in detective novels. The second is that Christie used the unreliable narrator technique to manipulate readers and deceive them.